2008
DOI: 10.1177/0960327108090269
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of selected skin decontaminant products and regimens against VX in domestic swine

Abstract: An anesthetized domestic swine model was used to compare the efficacy and cross-contamination potential of selected skin decontaminant products and regimens against the chemical warfare agent, VX. Animals topically exposed to 2×, 3× or 5× LD50 VX showed typical signs of organophosphate nerve agent poisoning, including miosis, salivation, mastication, dysrhythmias, and respiratory distress prior to death. Animals were exposed to 5× LD50 VX and then decontaminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 17 publications
5
35
0
Order By: Relevance
“…Subsequent histology revealed CNS pathology not unlike that seen following high dose exposure to the nerve agent soman (see Appendix A). While experimental procedures vary across studies, the absorbed dose administered to this subject is well below the LD50s of 79.6 g/kg for percutaneous VX in swine (Bjarnason et al, 2008), 60 g/kg reported for the white pig (from Chilcott et al, Fig. 3.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Subsequent histology revealed CNS pathology not unlike that seen following high dose exposure to the nerve agent soman (see Appendix A). While experimental procedures vary across studies, the absorbed dose administered to this subject is well below the LD50s of 79.6 g/kg for percutaneous VX in swine (Bjarnason et al, 2008), 60 g/kg reported for the white pig (from Chilcott et al, Fig. 3.…”
Section: Discussionmentioning
confidence: 73%
“…Finally, we decontaminated the site after exposure using reactive skin decontamination lotion (RSDL) to ensure sufficient safety of the exposures that is necessary to conduct moderately long-term evaluations with the subjects. RSDL is approved by the US Food and Drug Administration for chemical decontamination and its use has been shown to be an effective decontamination procedure for VX (Bjarnason et al, 2008;Lundy et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The response time is an important factor which infl uences the effectiveness of the decontamination (15,17,25,26). In this study, decontamination was performed 2 min after exposure and the effectiveness would have certainly been decreased had the treatment been delayed.…”
Section: Decontamination Of Opmentioning
confidence: 95%
“…Deaths were either fewer or associated with higher doses of OPs. All of the detergents provided a low or modest level of protection, which was attributed to their low detoxifi cation potency (17,18) and the low solubility of lipophilic OPs in water solutions (2,17). The lowest decontamination effectiveness was achieved against paraoxon (PR=1.6 to 2.6), followed by soman (PR=2.6 to 3.6).…”
Section: Decontamination Of Opmentioning
confidence: 99%
“…Detergents and detergent-based mixtures are commonly used as additives to water for mass decontamination as an emergency response to mass chemical industrial accidents or terrorist attacks [1,2]. A generic method for mass casualty decontamination involves a whole body wash with water and/or detergent-based washing solutions.…”
Section: Introductionmentioning
confidence: 99%